Traffic Flow Analysis Over a IPv6 Hybrid Manet (2017)
The Mobile Ad-hoc NETworks (MANET) consist of a spontaneous association of a group of nodes that dynamically change their position and exchange data between each other, regarded as autonomous network segments with flat address schemes. However, its study has shown the benefits obtained by interconnecting them to fixed network segments and Internet. This article will revise by means of using a simulation tool, the behavior of the data transmissions between the fixed network segment, a reactive gateway and the IPv6 MANET, whose nodes show a high degree of mobility, such as vehicles in an urban environment.